Individual Factor Predictor and Organizational Factor Predictor to Detect Potential Corrupt Behaviour - Syafri, Nida Ulhidayah; Sayyidina, Nadila Azzahra; Sari, Muhammad Charisma Sembahen Martdian Ratna; Maulana, Noveri (Asia Pacific Fraud Journal, 2024)
KPK known as an institution that eradicates corruption, they receive reports of indications of corruption and conducts arrest operations (OTT) to be followed. This shows that corruption occurs every day, and this act of corruption will not be able to be eradicated if it only relies on KPK. Efforts are needed from each individual organization in preventing corruption from occurring. This research examines individual factors (flexing, life style and love of money) and organizational factors (internal control, whistle blowing, anti-fraud awareness, law enforcement and leadership style) which are expected to be predictors of someone behaving corruptly. This research using quantitative approach and the data was collected using a questionnaire which Indonesian employees as a respondents. After testing, it was found that flexing, lifestyle, love of money, internal control, whistleblowing and anti-fraud awareness were able to become predictive factors for someone to commit corruption. Thus, based on the results of this research, organizations can focus on designing policies and training / coaching programs to prevent corrupt behavior in employees.Â